The Correlation Between Principal's Transformational Leadership And Emotional Intelligence With Job Satisfaction - Sutji Harijanto; Hasan Padili; Griet Helena Laihad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study uses a survey method with correlational research consisting of two independent variables, namely transformational leadership and emotional intelligence and one dependent variable, namely teacher job satisfaction. This research was conducted on SD Negeri Se-Cluster 03, District of Rawamerta-Kabupaten Karawang, with a population of 170 teachers and 119 samples were selected using proportional random sampling. The data analysis used is normality test, simple regression, multiple regression, homogeneity, simple correlation, multiple correlation, and partial correlation. The results obtained are as follows: First, there is a significant positive relationship between the principal transformational leadership variable (X1) and teacher job satisfaction (Y) which is expressed in the form of a correlation coefficient: ry1 = 0.5074 regression equation = 52.495 + 0.631 X1, and the coefficient of determination r2y1 = 0.2574. Second, there is a significant positive relationship between the emotional intelligence variable (X2) and teacher job satisfaction (Y) which is expressed in the form of a correlation coefficient: ry2 = 0.5800, the regression equation = 50,953 + 0.606X2, and the coefficient of determination r2y2 = 0, 3364. Third, there is a significant positive relationship between the variables of the principal's transformational leadership (X1) and emotional intelligence (X2) together with teacher job satisfaction (Y) which is expressed in the form of a correlation coefficient ry1.2 = 0.6695, the regression equation = 12.9487 + 0.4405X1 + 0.4834X2, and the coefficient of determination r2 = 0.4482. Based on these things, it can be concluded that teacher job satisfaction can be increased through the principal's transformational leadership and emotional intelligence.